2007
DOI: 10.1002/chin.200739264
|View full text |Cite
|
Sign up to set email alerts
|

The History of Alamethicin: A Review of the Most Extensively Studied Peptaibol

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 76 publications
0
61
0
Order By: Relevance
“…T2, the fungus was grown in several types of broth media. Growth of the fungus in a modified potato dextrose broth (PDB) resulted in the generation of numerous new and known members of the malettinin family of polyketides [malettinins A (27), B (28), and F-H (16)(17)(18)(19)(20), respectively] ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…T2, the fungus was grown in several types of broth media. Growth of the fungus in a modified potato dextrose broth (PDB) resulted in the generation of numerous new and known members of the malettinin family of polyketides [malettinins A (27), B (28), and F-H (16)(17)(18)(19)(20), respectively] ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…The peptaibols have been intensively studied because of their abilities to form pores in the outer membranes of cells; these pore-forming capabilities result in most compounds in this class exhibiting nonspecific cytotoxic properties toward bacterial, fungal, and mammalian cells (15,17). The effects of peptaibols on mammalian cells tend to be relatively modest, causing the loss of cell viability at concentrations in the mid-to-high micromolar range (18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Significancementioning
confidence: 99%
“…Alamethicins (ALMs) belong to a family of antibiotic peptides (peptaibols) of fungal origin that are known to selfassociate upon binding to lipid membranes (reviewed in (1)(2)(3)(4)(5)(6)(7)(8)). The most extensively studied isoform, ALM F50/5, is characterized by a linear sequence of 19 amino acids, eight of which are a-aminoisobutyric acid residues.…”
Section: Introductionmentioning
confidence: 99%
“…38 The mode of action of alamethicin is considered to be through its effect on biomembrane systems by ion channel formation in lipid-membranes bilayers. 17,39,40 It was reported that alamethicin seems to form ionic channels on chromaffin cells, which are permeable to Ca 2+ , Mn 2+ and Ni 2+ . 41 Dathe et al 42 reported that alamethicin induces catecholamine secretion from chromaffin cells and enhanced metabolic activity in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…50 We showed that antitrypanosomal activity of the peptide antibiotics discussed have cationic and lipophilic character in the structure (Figure 1) and also these antibiotics have any of the b-sheet, a-helical or loop conformations. 17,43,51 Therefore, these peptides might act more selectively on T. brucei than mammalian cells, in spite of their toxicity. In the case of leucinostatin A, it has been reported that leucinostatin A-loaded nanospheres show anti-Candida albicans activity both in vitro and in vivo, but with drastic reduction of toxicity.…”
Section: Discussionmentioning
confidence: 99%